A Method for Approximating the Nodal Modulations of Real Tides - Amin, M. (The International Hydrographic Review, 2015)
A simple method for approximating the nodal modulations of tidal constituents generated in shallow waters is described. The changes in the nodal modulations from their equilibrium values are found to be mostly due to bottom friction. In this method, functional approximations of interaction coefficients are obtained with the help of resolved non-linear tides of frictional origin. New nodal terms and contributions to the nodal terms of gravitational origin are estimated by using the interpolated values of interaction coefficients for respective frequencies. Four years of observations can provide a reasonably accurate estimate of nodal terms and nodal modulations as such, which normally requires at least 18.6 years of observations. Tidal predictions are shown to be quantitatively improved when newly derived modulations are used in place of the conventional equilibrium modulations.